The "CROMa" Project: A Care Pathway for Clinical Management of Patients with Bisphosphonate Exposure - Mauro Capocci; Umberto Romeo; Fabio Cocco; Isabella Bignozzi; Susanna Annibali; Livia Ottolenghi (Hindawi Limited, 2014)
Aim. To describe 7 years of activity of "CROMa" (Coordination of Research on Osteonecrosis of the Jaws) project of "Sapienza" University of Rome. Materials and Methods. A preventive and therapeutic care pathway was created for patients with bisphosphonates (BPs) exposure. Demographic, social, behavioural, pharmacological, and clinical variables were registered in a dedicated database. Results. In the project, 502 patients, 403 females and 99 males, were observed. Bone pathologies were 79% osteometabolic diseases (OMD) and 21% metastatic cancer (CA). Females were 90% in OMD group and 41% in CA. BP administration was 54% oral, 31% IV, and 11% IM; 89% of BPs were amino-BP and 11% non-amino-BP. Consistently with bone pathology (OMD/CA), alendronate appears to be prevalent for OMD (40% relative), while zoledronate was indicated in 92% of CA patients. Out of 502 cases collected, 28 BRONJ were detected: 17 of them were related to IV BP treatment. Preventive oral assessment was required for 50% of CA patients and by 4% of OMD patients. Conclusions. The proposed care pathway protocols for BP exposed patients appeared to be useful to meet treatment and preventive needs, in both oncological and osteometabolic diseases patients. Patients' and physicians' prevention awareness can be the starting point of a multilevel prevention system.